The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1089/end.2020.0708
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learnt (Clinical Outcomes and Cost Savings) from Virtual Stone Clinic and Their Application in the Era Post-COVID-19: Prospective Outcomes over a 6-Year Period from a University Teaching Hospital

Abstract: Introduction: We introduced a nurse-led telephone-based virtual stone clinic (VSC) follow-up for the surveillance of patients with asymptomatic renal calculi or those at a high risk of recurrent kidney stone disease (KSD). The aim of this study was to look at the outcomes of VSC and its role in the post-COVID era. Methods: Prospective outcomes audit was done for all patients referred to the VSC for a 6-year period (March 2014-April 2020). VSC is led by specialist stone nurses for ongoing surveillance of KSD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Several studies from the solid tumor literature have demonstrated innovative virtual programs for delivering cancer services that have reduced the cost and time burden of appointments. 24 A study of Veterans receiving follow-up for pulmonary nodules found a 47% cost decrease when a visit was virtual compared with in-person (from $228 to $120 USD), and an average travel avoidance of 86 miles (138.4 km) per patient. 25 These results are similar to those described in our study, in which we found an average savings of 121.1 minutes and an opportunity cost-savings of $133.10 CAD (SD $102.10 CAD) per patient per visit.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from the solid tumor literature have demonstrated innovative virtual programs for delivering cancer services that have reduced the cost and time burden of appointments. 24 A study of Veterans receiving follow-up for pulmonary nodules found a 47% cost decrease when a visit was virtual compared with in-person (from $228 to $120 USD), and an average travel avoidance of 86 miles (138.4 km) per patient. 25 These results are similar to those described in our study, in which we found an average savings of 121.1 minutes and an opportunity cost-savings of $133.10 CAD (SD $102.10 CAD) per patient per visit.…”
Section: Discussionmentioning
confidence: 99%
“…The everyday practice has been tremendously changed both in hospital and ambulatory care. The measures taken to advance patient safety triggered a prompt application of telemedicine and information technology systems, which otherwise would have been pending their implementation for another decade [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hughes et al ( 14 ) in their study established the feasibility of video visits by patients as opposed to in-person visits and used the metric of “revisit” rates to determine success. They found that revisit rates were more when the initial visit was in an in-patient setting as compared to a virtual clinic approach.…”
Section: Procedure-related Concernsmentioning
confidence: 99%